Bilingual education for young children: review of the effects and consequences - Bialystok, Ellen (Int J Biling Educ Biling, 2016)
Bilingual education has been an educational option in many countries for over 50 years but it remains controversial, especially in terms of its appropriateness for all children. The present review examines research evaluating the outcomes of bilingual education for language and literacy levels, academic achievement, and suitability for children with special challenges. The focus is on early education and the emphasis is on American contexts. Special attention is paid to factors such as socioeconomic status that are often confounded with the outcomes of bilingual education. The conclusion is that there is no evidence for harmful effects of bilingual education and much evidence for net benefits in many domains.